CCP initial margin models in Europe - Ismael Alexander Boudiaf; Martin Scheicher; Francesco Vacirca (European Central Bank (ECB), 2023)
In this paper we aim to provide a holistic understanding of the Initial Margin (IM) models used by Central Counterparties (CCPs) in Europe. In addition to discussing their relevance in terms of CCP risk management and their importance for the functioning of financial markets, we provide an overview of the main modelling frameworks used, including Standard Portfolio Analysis of Risk (SPAN) and Value at Risk (VaR) models.By leveraging on publicly available data, we provide an up-to-date picture of current modelling practices for specific cleared product classes, as well as various trends in IM modelling practices in Europe. We show how IM model frameworks vary materially, depending on the CCP's past choices and the products it clears. Despite a propensity to switch to VaR models, idiosyncrasies and differences across CCPs are likely to persist.We conclude by highlighting current and upcoming challenges and risks to CCP IM model frameworks and linking the current status quo with ongoing and upcoming regulatory work at European and international level.
Keywords: G15; G18; G19; G23; G28; G32; 330; Central Counterparties; initial margin models; risk management; modelgovernance and validation